Sterols and Other Metabolites from Freshwater Microalga Chlorococcum infusionum (Schrank) Meneghini - Ragasa, Consolacion Y.; Mandia, Emelina H.; S. Tan, Maria Carmen; Oyong, Glenn G.; Madrazo, Cynthia F.; Ubando, Aristotle T.; Culaba, Alvin B.; Shen, Chien-Chang (Asian Journal of Chemistry, 2020)
Chemical investigation of the dichloromethane extract of Chlorococcum infusionum afforded a mixture of chondrillasterol (1) and 22-dihydrochondrillasterol (2) in a 3:1 ratio as the major sterols, and lutein (3), triacylglycerols (4), fatty acids (5) and hydrocarbons (6) as the minor compounds. The structures of compounds 1 and 2 were elucidated by extensive 1D and 2D NMR spectroscopy, while compounds 3-6 were identified by comparison of their NMR data.